Spray drying of liquid extracts of curcumin : process performance and product quality properties. (2017)
(Eng) The aim of this work was to evaluate the operation of spray drying to obtain powder curcumin from turmeric extract blended with maltodextrin. An experimental design (central composite design) with two statistical factors was used. These factors were the inlet air temperature (140-160ºC) and outlet air temperature (75-95ºC), with the rotation speed kept constant (28000 RPM). Statistical optimization was established by considering the response surfaces analysis where the hygroscopicity was minimized and the curcumin concentration was maximized. The optimal conditions for the spray drying process were inlet and outlet air temperatures of 149ºC and 75ºC, respectively, at an atomization speed of 28000 RPM. These settings provided the following results: hygroscopicity (11.71% ± 0.03) and final concentration of curcumin (9.03 ± 0.44 mg/g), which were statistically significant.